2013
DOI: 10.1080/17429145.2013.765043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought and subsequent rewatering on Rumex obtusifolius leaves of different ages: reversible and irreversible damages

Abstract: Solute leakage from leaves can be high, especially under abiotic stress. As climate models project higher drought risks for future summers in Central Europe, the more frequent and more severe drought stress periods might cause increased leakage. Solute leakage under drought and subsequent rewatering was tested in the weed Rumex obtusifolius. A strong increase in leakage from leaves was found in response to drought. Older leaves leaking high amounts of solutes after 17 days of drought were not able to recover a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One of the aims of our study was to analyze whether the exogenous application of BRs might differently mitigate the negative impact of drought on plants in two different leaves: those that were already fully developed at the beginning of stress and those that were still developing during stress period. Several authors (Mostajeran and Rahimi-Eichi, 2009;Gilgen and Feller, 2014;Budičet al, 2016) found that older leaves are more affected by Frontiers in Plant Science frontiersin.org drought than younger leaves. However, in relation to the BRs role in plant drought response, this aspect has not been previously examined.…”
Section: Effects Of Exogenous Br Application On Leaves Of Different Agementioning
confidence: 99%
“…One of the aims of our study was to analyze whether the exogenous application of BRs might differently mitigate the negative impact of drought on plants in two different leaves: those that were already fully developed at the beginning of stress and those that were still developing during stress period. Several authors (Mostajeran and Rahimi-Eichi, 2009;Gilgen and Feller, 2014;Budičet al, 2016) found that older leaves are more affected by Frontiers in Plant Science frontiersin.org drought than younger leaves. However, in relation to the BRs role in plant drought response, this aspect has not been previously examined.…”
Section: Effects Of Exogenous Br Application On Leaves Of Different Agementioning
confidence: 99%
“…(broadleaf dock) compared with its aerial parts has been reported by Gilgen and Feller (2013). The allocation of solutes to the roots helps R. obtusifolius plants to recover quickly from drought stress; this rapid recovery is a key factor for overall plant performance and competitiveness against other species, especially under stress (Gilgen and Feller, 2013, 2014).…”
Section: Weeds Drought and High Temperaturesmentioning
confidence: 99%
“…The number and the area of active leaves per plant is important for the overall performance of a plant (Munne-Bosch and Alegre, 2004). The formation and expansion of young leaves and senescence of old leaves are equally important in this context (Lefi et al, 2004;Simova-Stoilova et al, 2010;Mahdid et al, 2011;Gilgen and Feller, 2014). The catabolism of proteins in older leaves allows a redistribution of nitrogen from senescing tissues to other plant parts (Feller and Fischer, 1994), while the small percentage of nitrogen present in chlorophyll remains in modified form in the vacuoles of senescing or senesced cells (Hörtensteiner, 2006).…”
Section: Leaf Survival and Altered Timing Of Senescencementioning
confidence: 99%